An Empirical Comparison of the Profiles of Security Threat Group Offenders with General Offenders - Leuprecht, Christian (International journal of offender therapy and comparative criminology, 2025)
Datasets of offender attributes, both pre-custody and in-custody, were provided by the Correctional Service of Canada with the goal of exploring whether Security Threat Group (STG) offenders (informally, gang members of various kinds) differ in any systematic way from other offenders. For pre-custody attributes, we show that the entire offender population varies along two almost independent axes, one associated with affinity for violence, and the other with affinity for substance abuse. Within this structure, STG offenders are characteristically less extreme, in either direction, than the general offender population. For approximately two dozen attributes, STG offenders, as a group, tend to have higher values; for a few, they tend to have lower values. For in-custody attributes, the entire offender population forms a triangular structure whose vertices represent: passivity; violence and troublemaking; and involvement in programs leading to partial release. The differences between the STG offender population and the general offender population are small. An offender who is placed at the high end of the propensity for violence axis and/or the high end of the substance abuse axis based on pre-custody attributes is much more likely to be involved in incidents, grievances, and violence while in custody. This may have implications for risk stratification of incoming offenders.